Effects on gut morphology and microflora of broiler chicken fed with different levels of fermented palm kernel cake - Mohd Bazari, Nisa Nadirah (2016)
Agricultural byproducts such as Palm kernel cake (PKC) could be used to substitute commercial feed ingredients such as maize and soybeans in poultry diets. PKC is very fibrous and have high levels of non-starch polysaccharides (NSPs). Simple stomach of monogastric animal limit the use of PKC in their feeds due to lo fiber digestive enzyme in the gastrointestinal tract. However, the PKC nutritive quality can improve by cellulolytic microbes through Solid State Fermentation (SSF). Through the method, the concentration of crude protein has increased while the crude fibre has decreased. The fermented PKC (FPKC) used in the experiment was fermented by using P. polymyxa ATCC 842.The digestion and absorption of nutrients efficiency in poultry are depends on the microflora in the gut. Diet has been shown to be one of the major factors that influence the microbial activity in gastrointestinal tract of poultry. Lactic acid bacteria (LAB) and Enterobacteriaciae (ENT) have been reported to be the normal flora that lives in the gastrointestinal tract and mainly found in the duodenum, ileum and caecum. LAB are gram positive, non-spore forming and predominantly anaerobic bacteria, occurring as beneficial microflora in gastrointestinal tract in the avian species. LAB plays a major role to ferment carbohydrates or starch to produce lactic acid and hydrogen peroxide as an end product. Increase in size and height of intestinal villi shows that the nutrient absorption in the gastrointestinal is more effective. A study was conducted to examine the effects of feeding fermented palm kernel cake (FPKC) on gut morphology and microflora counts of broiler chicken. Two hundred and seventy of day-old male chicks were randomly assigned into 54 cages. From days 21 to 42, broiler chickens were fed based on the dietary treatments. Treatment 1 (T1) was kept as a control, Treatment 2 (T2), Treatment 3 (T3), Treatment 4 (T4) and Treatment 5 (T5) containing 5%, 10%, 15% and 20% of PKC respectively. Treatment 6 (T6), Treatment 7 (T7), Treatment 8 (T8) and Treatment 9 (T9) containing 5%, 10%, 15% and 20% of FPKC respectively. The faecal LAB counts had significantly more in the birds from T7 (P<0.05) among all the dietary treatments while faecal ENT counts for the birds from T6 was the lowest (P<0.05) as compared to other treatments. Birds fed with FPKC showed increase in villus height and crypt depth of small intestines (duodenum, jejunum and ileum). Increase in LAB counts, villus height and crypt depth results in efficient nutrients absorption. From this study, it can be concluded that inclusion of FPKC in the broiler diets could increase the population of LAB and reduces the ENT population in the gastrointestinal tract, increase in villus height and crypt depth of the small intestines.